Physiological mechanisms to ensure accuracy and coordination of movement under conditions of unstable equilibrium and moving target (the case of strikes in sports karate); Теория и практика физической культуры; Т. 12 - Kapilevich L. V. Leonid Vladimirovich; Guzhov F. A.; Bredikhina Yu. P.; Ilyin A. A. (2014, 2014)
Title screen